PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI DIMEDIASI KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU (STUDI KASUS PADA GURU SMP NEGERI DI KECAMATAN MARGOREJO KABUPATEN PATI) THE INFLUENCE OF WORK MOTIVATION AND ORGANIZATIONAL CULTURE MEDIATED BY COMMITME - Sudriningsih, 1252020023; Liana, . Lie (Jurnal Mahasiswa Pasca Sarjana, 2014)
The aim of this study is to identify and analyze the influence of work motivation and organizational culture Â mediated by the organizational commitment to the teacher performance. This study used an entire population, that is called census method (saturated sample). The researchÂ population is all teachers at Yunior High School in Margorejo Pati regency as many asÂ 85 people. The analyze method used in this study include testing the validity of the factor analysis, reliability tests with Cronbach alpha formula, the multiple regression analysis, and tests of significance, the coefficient of determination to validate the research hypothesis and regression testing mediation. The results stated that work motivationÂ has no effect on organizational commitment. Variable organizational culture has a positive and significant impact on organizational commitment. Organizational commitment does not affect the teacherÂ performance. Work motivation has a positve and significantÂ effect on teacher performance. Organizational culture variables do not affect theÂ teachers performance. Organizational commitment doesnât have a significance influenceÂ on teacher performance through the mediating variable of organizational commitment. Organizational commitment does not mediate organizational culture on teacher performance. Keywords : Work Motivation, Organizational Culture, Commitment Organizational, and teacher performance.